Germany : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Germany. (IMF Staff Country Reports; Country Report ;, 2021)
Germany managed the first wave of the COVID-19 epidemic relatively well thanks to an early and vigorous public health response. Nonetheless, unprecedented disruptions to economic and social activity caused a deep recession in the first half of 2020. The gradual easing of containment measures since late-April has led to a partial revival of growth, but in late-October a 'lockdown light' was announced to counter a new wave of infections, and restrictions were further tightened in mid-December. Significant risks remain about the pace and extent of the recovery as the uncertain course of the epidemic continues to impact economic activity.